PENERAPAN MODEL MANAJEMEN MUTU TQM DAN ISO DALAM PENGELOLAAN PENDIDIKAN: PENERAPAN MODEL MANAJEMEN MUTU TQM DAN ISO DALAM PENGELOLAAN PENDIDIKAN - Fajrian Nanda Dwi Rezky; Sri Rahayu Amrina Rosyada; M. Sobry (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of Total Quality Management (TQM) and ISO quality management models in educational management. The main focus is on how TQM and ISO principles can be integrated to enhance the effectiveness, efficiency, and quality of educational services in formal educational institutions. This research employs a qualitative descriptive approach through document analysis, interviews, and observations of quality management practices in selected schools and universities. The findings indicate that the application of TQM and ISO significantly contributes to improving quality culture, teacher professionalism, and student satisfaction. However, the success of implementation largely depends on leadership commitment, stakeholder involvement, and the sustainability of evaluation and quality improvement programs. The study concludes that the synergy between TQM and ISO provides an effective strategy for developing a standardized, adaptive, and continuously improving educational management system.